Penerapan Data Protection Dengan Metode Replikasi Snapmirror Relationship Pada Perusahan XYZ - Mulya, Imam; Ramayanti, Desi; Gatsu, Puspita (Institut Agama Islam Negeri (IAIN) Curup, 2023)
The development of an IT infrastructure at this time is growing rapidly, plus a lot of data, company transactions are stored on the server and thus require external storage as a production data storage medium, such as transactions, employee payroll applications to email used by employees of PT. XYZ. However, there are obstacles such as data corruption on the server so that databases and applications stored on the server are lost and therefore a method is needed to protect data and back up data on the company, the method used is the snapmirror replication method. Where data on a server located in the DC (Data Center) is stored in external storage then the data is replicated on external storage located in the DRC (Disaster Recovery Center), which later the external storage will create a snapshot copy. And later it is hoped that with this snapmirror replication, if corrupt data occurs, it will be recovered properly.